Answer: x(x - 9) = 713
Explanation:
Let the first number be x and the second number be y.
From the first statement;
xy = 713 ............. equation 1
From the second statement , the first number is 9 more than the second number , this means that x is greater than y by 9 , in equation form , we have
x - y = 9 ............ equation 2
Combining the two equations , we have
xy = 713 ........... equation 1
x - y = 9 .......... equation 2
From equation 2 , make y the subject of the formula , that is
y = x - 9 ............ equation 3
substitute equation 3 into equation 1 , we have
x ( x - 9 ) = 713
which will result in a quadratic equation
- 9x = 713
- 9x - 713 = 0